English Language Teachers' Profile and Their Teaching Styles - Abdullah, Muhammad Kamarul Kabilan (2000)
English language teachers' teaching style(s) preferences are often the realization of the teachers' beliefs and attitudes towards the English language. These beliefs and attitudes of teachers will directly and indirectly influence the way students learn the language and, their success in learning it. Therefore, it is important to know who are the English language teachers, what are their teaching styles and, what perception do they have of other English language teachers and English language teaching. Relating to the above questions, this research describes the demographic variables of English language teachers and their perception of issues and trends in English language teaching in Malaysia. It also describes the teachers' teaching styles, and examines the relationships between teachers' teaching experience and teaching styles. The study was carried out in 14 secondary government schools in Sungai Petani, Kedah (n=108). Two sets of questionnaires were used: Language Teachers' Profile, developed by the researcher, based on Protherough & Atkinson (1992) and, Style Analysis Survey (Oxford 1993). It was found that the number of new English language teachers in the profession of teaching was dwindling very fast by the years. Schools lack qualified and trained English language teachers. In addition, teachers face students who show negative attitudes towards English language learning, and this was a serious problem for them. Teachers in this study display significant teaching styles i.e. visual, global, extroverted and closure-oriented. The study also found negative relationship between teachers' teaching experience and teaching styles (how teachers approach tasks).